William Safire papers - Safire, William, 1929-2009.; Safire, William, 1929-2009.; Safire, William, 1929-2009. an anecdotal dictionary of catchwords, slogans, and political usage
Correspondence, memoranda, diary notes, minutes of meetings, speeches, writings, reports, statements, notes, press releases, press conference transcripts, annotated press reports, briefing books, advertising material, photographs, and other papers chiefly documenting Safire's close association with Richard M. Nixon as public relations consultant, speechwriter, and political advisor from 1960 to 1973. Includes material relating to Nixon's 1960 presidential campaign, the 1966 general elections, the 1968 presidential campaign, and especially to Safire's role on the Nixon White House staff prior to the Watergate affair. Also includes material on Safire's work on Louis J. Lefkowitz's 1961 New York City mayoral campaign, Jacob K. Javits's 1962 Senate race, Nelson A. Rockefeller's 1964 presidential bid and 1966 New York gubernatorial reelection, and other Republican campaigns. Writings include drafts and notes for Safire's memoirs, Before the Fall: An Inside View of the Pre-Watergate White House (1975) and for his work on political terminology and lexicography, New Language of Politics: An Anecdotal Dictionary of Catchwords, Slogans, and Political Usage (1968).
Other persons represented include Spiro T. Agnew, Patrick J. Buchanan, Arthur F. Burns, Charles W. Colson, John Ehrlichman, H.R. Haldeman, Thomas Huston, Henry Kissinger, Daniel P. Moynihan, Richard Nathan, Raymond K. Price, William P. Rogers, and George Pratt Schultz.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Author, journalist, speechwriter, and public relations consultant. Also known as William L. Safire.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Agnew, Spiro T., -- 1918-1996.; Buchanan, Patrick J. -- 1938-; Burns, Arthur F. -- 1904-1987.; Colson, Charles W; Ehrlichman, John; Haldeman, H. R. -- 1926-1993.; Huston, Thomas; Javits, Jacob K. -- 1904-1986.; Kissinger, Henry, -- 1923-; Lefkowitz, Louis J; Moynihan, Daniel P. -- 1927-2003.; Nathan, Richard, -- 1935-; Nixon, Richard M. -- 1913-1994.; Price, Raymond K. -- 1930-; Rockefeller, Nelson A. -- 1908-1979.; Rogers, William P. -- 1913-2001.; Shultz, George Pratt, -- 1920-; United States. -- White House Office; Republican Party (U.S. : 1854- ); Elections -- New York (State) -- 1962.; Governors -- New York (State) -- Election -- 1966.; Mayors -- New York (State) -- New York -- Election; Lexicography; Presidents -- United States -- Election -- 1960.; Presidents -- United States -- Election -- 1964.; Presidents -- United States -- Election -- 1968.; Presidents -- United States -- Staff -- 1969-1974.; Speechwriting; United States -- Politics and government -- 1969-1974.; United States -- Politics and government -- Dictionaries; Authors; Journalists; Public relations consultants; Speechwriters